Successful long-term results (> 5 years) of superselective transarterial chemoembolization in symptomatic/enlarging liver hemangiomas: a paradigm shift at a hepatopancreatobiliary surgery unit - Özden, İlgin; Poyanlı, Arzu; İbiş, Cem; Acunaş, Bülent (Frontiers in Medicine, 2026)
BackgroundThe favorable experience with superselective transarterial chemoembolization (TACE) using lipiodol-bleomycin may lead some hepatopancreatobiliary surgery centers to offer it as first-line treatment for symptomatic/enlarging hemangiomas.Patients and methodsThe charts of 56 patients treated at a university hospital between 2012 and 2018 were reviewed. The results were reported as median (range).ResultsThe indication was abdominal pain in 46 patients (concomitant enlargement in 12, enlargement and fever in 1), asymptomatic enlargement in 8 and possibility of adverse hemodynamic consequences in two. A single session was planned for 48 patients and two-sessions in 8; in addition, four patients required 2 (n: 2) or 3 (n: 2) sessions for symptom control. Six patients (11%), experienced post-embolization syndrome lasting longer than one week. Lesion volume decreased from 586 (147–8,435) cm3 to 332 (24–4,710) cm3 in 4 (2–8) months after the first session [p < 0.01; 46% (5–92) regression]. In the 8 patients who underwent two planned sessions, lesion volume decreased from 1,454 (441–8,435) cm3 to 661 (159–3,716) cm3, 5 (3–7) months after the second session [62% (37–78) regression]. Shrinkage in the 95%–99% range was observed in 13 (25%) of the 51 patients who were followed at least one year. Thirty-four (73%) of the 46 symptomatic patients reported resolution/marked amelioration of symptoms. No late complications were observed in 41 patients (73%) followed for at least 5 years; progressive regression was observed in 36 (88%) cases; in two patients (5%), initial regression was followed by regrowth.ConclusionTACE is a successful first-line treatment for patients with symptomatic/enlarging hemangiomas. Better assessment of the quality of life in symptomatic patients and different definitions of success in cases with symptomatic and asymptomatic progressive enlargement are required.